Does category of strength predict return-to-work after occupational injury? - Chia-Lin Yang; Yan-Ru Yin; Chuan-Man Chu; Pei-Ling Tang (BMC, 2022)
Abstract Background Occupational accidents may lead laborers to lose their working capacities, affecting their physical and mental health. Occupational rehabilitation helps improve the ability of patients with occupational accidents and suggests appropriate jobs to avoid second injuries. This study aimed to identify whether any of the functional capacity evaluation (FCE) strength subtests predicted successful return to work. Methods Data were collected of 84 patients receiving government-subsidized occupational rehabilitation between September 2016 and December 2018. A structured questionnaire was employed for pre- and post-training assessment, including basic information, information of the occupational accident, status of the laborer at the opening of the injury case, physical requirement for the job, and physical capacity. Eight subtests of strength were included in the physical capacity evaluation, i.e., carrying, lifting to several levels, power grip, and lateral pinch, to explore the association between the strength tests and return to work. Results The unadjusted model showed that for every additional kilogram in bilateral carrying strength before work hardening training, the odds of successful return to work increased (crude odds ratio [OR] = 1.12, 95% confidence interval [CI] = 1.01-1.24, p = 0.027). After adjustment for basic demographic information and pre-accident physical functional elements of work, the odds of successful return to work increased (adjusted OR = 1.27, 95% CI = 1.04-1.54, p = 0.02) for every additional kilogram in the pre-training bilateral carrying strength. There were no statistically significant differences observed in the other seven subtests. Conclusion Through thorough evaluation and work hardening training provided in the occupational rehabilitation, patients' physical capacity can be understood and improved. However, a full evaluation of functional capacities is prolonged and time-consuming. This study provides evidence that pre-work-hardening bilateral carrying strength may be a promising predictor of return to work and we recommend to consider it as a prioritized test to assist in determining appropriate advice regarding return to work.